EFFECTS OF STABILIZATION EXERCISES IN ADDITION TO ROUTINE PHYSICAL THERAPY IN ELDERLY PATIENTS WITH BACK PAIN; A RANDOMIZED CONTROLLED TRIAL - Muhammad Shahid; Mohammad A Mohseni Bandpei; Ashfaq Ahmed (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Back pain is a prevalent musculoskeletal condition among the elderly, which significantly impacts their quality of life. Physical therapy is a common treatment option for back pain, but the addition of specified treatment such as stabilization exercises may improve outcomes for elderly patients. Methods: This 18-month single-blind, randomized controlled trial was conducted at Banu Bai Physiotherapy Centre in Karachi, Pakistan. The study had a sample size of 72, 36 participants per group, determined using Noordzij et al.’s (2010) formula. Participants, aged 60 or older with chronic back pain, were randomly assigned to stabilization exercise (SE) group or routine physical therapy (RPT). In addition, both groups participated in co-interventions and home exercise programs, with 45-minute treatment sessions. Results: The average age was 71.5 years, and the average BMI was 27.4. Both groups showed similar demographic and medical characteristics at baseline. After the intervention, the SE group showed a significant improvement in all endurance test outcomes, including trunk flexors (p=0.003), trunk extensors (p=0.004), trunk right side flexors (p=0.007), and trunk left side flexors (p=0.005), compared to the RPT group. The SE group also showed a significant improvement in spinal mobility (p=0.013). Conclusion: Adding stabilization exercise therapy to routine physical therapy can significantly improve trunk muscle endurance and spinal mobility in elderly patients with back pain. These findings suggest that healthcare professionals should consider incorporating stabilization exercises into their practices to optimize back pain management in this population. Further research is needed to explore the long-term effects of stabilization exercises and compare their effectiveness with other exercise therapies.